INFLUENCE OF WEATHER CONDITIONS ON THE DURATION OF THE PRE-EMERGENCE PERIOD AND FORMATION OF WINTER TRITICAL SEEDLINGS DENSITY - Худолей, Людмила; Барановский, Олег; Свистунова, Ирина; Полторецкий, Сергей (SWorldJournal, 2021)
This article presents the results of research to study the impact of technological methods of cultivation on the duration of the pre-emergence period and the formation of seedling density of winter triticale. It is established that the most expedient is t